FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PERSONAL HYGIENE SAAT MENSTRUASI PADA SISWI KELAS XI DI SMA N 14 PEKANBARU - Wira Ekdeni Aifa; Nia Desriva (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Adolescence is a period of transition between childhood and adulthood which is marked by physical, emotional and psychological changes. Adolescence, which is between the ages of 10-19 years, is a period of maturation of the human reproductive organs, and is often called puberty. Menstruation is cyclic bleeding from the uterus. The length of the menstrual cycle is the distance between the start of the last menstrual period and the start of the next menstruation. The day the bleeding starts is called the first day of the cycle. The normal length of the menstrual cycle is considered a classic cycle is 28 days, but the variation is quite wide, not only between the same women. More than 90% of women have a menstrual cycle between 24 to 35 days. Personal hygiene is self-care that is carried out to maintain health both physically and psychologically. This study aims to determine the factors associated with personal hygiene behavior during menstruation in class XI students at SMA 14 Pekanbaru. This research is a descriptive analytic study with a cross sectional design. The population in this study were all young women of SMA 14 Pekanbaru in Class XI, which amounted to 61 people. The results of the analysis showed that there was a significant relationship between knowledge (p value = 0.000), sources of information (p value = 0.000), parents' income (p value = 0.020), and personal hygiene behavior during menstruation at SMA 14 Pekanbaru. It is hoped that this research can provide knowledge and information for all young women. Keywords: Adolescents, Menstruation, Personal Hygiene